2023
DOI: 10.1186/s12014-023-09396-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the serum proteomic and fecal metaproteomic to analyze the impacts of overweight/obesity on IBD: a pilot investigation

Abstract: Background Inflammatory bowel disease (IBD) encompasses a group of chronic relapsing disorders which include ulcerative colitis (UC) and Crohn’s disease (CD). The incidences of IBD and overweight/obesity are increasing in parallel. Here, we investigated alterations in proteomic in serum and metaproteomic in feces of IBD patients with overweight/obesity and aimed to explore the effect of overweight/ obesity on IBD and the underlying mechanism. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…This type of cut-off is very common in metaprotoemic workflows. [18][19][20]41,42 The Peptonizer results attribute all highest scores to the correct taxa. Since they represent a probability distribution, introducing a 'cut-off' probability for present taxa does not make sense mathematically, but will often be necessary for practical reasons.…”
Section: Taxonomic Composition Results For the Sihumix Samplementioning
confidence: 99%
“…This type of cut-off is very common in metaprotoemic workflows. [18][19][20]41,42 The Peptonizer results attribute all highest scores to the correct taxa. Since they represent a probability distribution, introducing a 'cut-off' probability for present taxa does not make sense mathematically, but will often be necessary for practical reasons.…”
Section: Taxonomic Composition Results For the Sihumix Samplementioning
confidence: 99%
“…Among the above characteristics, the relative abundance of P. distasonis, the most critical microbial feature, increased significantly after the intervention. Previous studies have identified a decrease in the abundance of P. distasonis in obese and metabolic syndrome populations [37,38]. Additionally, other studies of dietary interventions for treating obesity have shown an upward trend in the relative abundance of P. distasonis after the intervention.…”
Section: Machine Learning Identifies Key Microbial Changes Before And...mentioning
confidence: 94%
“…Numerous studies have established the presence of dysbiosis in individuals with IBD, demonstrating reduced bacterial diversity particularly during flares, and the possibility of normalization of bacterial microbiota after long periods of remission [11]. A recent study integrated serum proteomic and fecal metaproteomic analyses to examine the effect of overweight and obesity on these profiles in IBD, demonstrating that ulcerative colitis and Crohn's disease displayed similar serum molecular profiles in the setting of overweight or obesity, but that the presence of overweight/obesity disparately impacted gut microbiota composition in ulcerative colitis vs. Crohn's disease [12 ▪ ]. Interestingly, overweight/obesity appeared to enhance microbial diversity in ulcerative colitis, particularly increasing the abundance of certain organisms with the potential to serve as probiotics (e.g., Parabacteroides distasonis , Alistipes indistincus , and Ruminococcus bromii) .…”
Section: Pathogenesis Of Inflammatory Bowel Disease and Obesitymentioning
confidence: 99%
“…It is not known whether this suggests overweight/obesity may portend a protective microbial environment in ulcerative colitis, or if rather overweight/obesity status indicates a less severe disease course of their ulcerative colitis. Comprehensive multiomics studies such as these are helpful to shed light on the molecular underpinnings of IBD, the influence of microbiota, and the added impact of overweight/obesity [12 ▪ ].…”
Section: Pathogenesis Of Inflammatory Bowel Disease and Obesitymentioning
confidence: 99%